Diagnostic criteria for adult‐onset leukoencephalopathy with axonal spheroids and pigmented glia due to CSF1R mutation. (19th October 2017) - Konno, T.; Yoshida, K.; Mizuta, I.; Mizuno, T.; Kawarai, T.; Tada, M.; Nozaki, H.; Ikeda, S.‐I.; Onodera, O.; Wszolek, Z. K.; Ikeuchi, T.
Abstract : Background and purpose: To establish and validate diagnostic criteria for adult‐onset leukoencephalopathy with axonal spheroids and pigmented glia (ALSP) due to colony‐stimulating factor 1 receptor ( CSF1R ) mutation. Methods: We developed diagnostic criteria for ALSP based on a recent analysis of the clinical characteristics of ALSP. These criteria provide 'probable' and 'possible' designations for patients who do not have a genetic diagnosis. To verify its sensitivity and specificity, we retrospectively applied our criteria to 83 ALSP cases who had CSF1R mutations (24 of these were analyzed at our institutions and the others were identified from the literature), 53 cases who had CSF1R mutation‐negative leukoencephalopathies and 32 cases who had cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) with NOTCH3 mutations. Results: Among the CSF1R mutation‐positive cases, 50 cases (60%) were diagnosed as 'probable' and 32 (39%) were diagnosed as 'possible, ' leading to a sensitivity of 99% if calculated as a ratio of the combined number of cases who fulfilled 'probable' or 'possible' to the total number of cases. With regard to specificity, 22 cases (42%) with mutation‐negative leukoencephalopathies and 28 (88%) with CADASIL were correctly excluded using these criteria. Conclusions: These diagnostic criteria are very sensitive for diagnosing ALSP with sufficient specificity for differentiation from CADASIL and moderate specificity for other leukoencephalopathies. Our results suggest that these criteria are useful for the clinical diagnosis of ALSP.